DIRECT COSTS CORRESPONDING TO VASCULOGENIC ULCER DRESSINGS PERFORMED IN A COMPREHENSIVE WOUND CARE UNIT - Ruiz, Paula Buck de Oliveira; Pinheiro, Gabriella; Lima, Antônio Fernandes Costa (Cogitare Enfermagem, 2022)
Objective: to assess the mean direct costs corresponding to vasculogenic ulcer dressings performed by Nursing professionals on patients treated at a Comprehensive Wound Care Unit. Method: A quantitative and exploratory-descriptive research study, conducted in March, August and September 2020 at a Comprehensive Wound Care Unit located in Vitória da Conquista, Bahia, Brazil. The costs were calculated multiplying the time spent (timed) by the professionals by the cost of direct labor, adding the costs of the inputs. Data analysis was performed by means of descriptive statistics. Results: The total mean direct costs were as follows: US$ 11.90 (SD±10.79) for outpatient dressings (n=42), US$ 7.22 (SD±8.69) for home dressings (n=22) and US$ 3.10 (SD±2.57) for hospital dressings (n=11), with a significant contribution from the costs of topical therapies: US$ 9.82 (SD±10.55), US$ 5.60 (SD±8.43) and US$ 1.30 (SD±0.22), respectively. Conclusion: the results may support a review of the inputs required for vasculogenic ulcer dressings, notably, regarding topical therapies and materials/solutions.